Incidence and pattern of childhood cancers in India: Findings from population-based cancer registries - MD Abu Bashar; J S Thakur (Indian Journal of Medical and Paediatric Oncology)
Childhood cancers have different characteristics than those occurring among adults and described as cancers occurring below 15 years of age. In developed countries, its incidence is relatively rare but it's a leading cause of death. More than 80% of the childhood cancers are occurring in low and middle income countries. Based on data from population based cancer registries under National Cancer Registry Programme, in this commentary, we described the incidence and pattern of Childhood cancers in India and its implications.